Basic financial management (Prenti-Hall International, 1996)
It offers an increased emphasis on the capital market's influence on corporate decisions, has an increased number of basic financial management inserts and incorporates a new section on readings in finance. It also suggests starting points for considering ethical issues related to financial decision-making, contains a new introductory section on capital markets, updates the section on taxes to reflect current tax revisions, compares basic differences in taxes across borders and discusses alternative methods for estimating a project's systematic risk through the use of accounting data as well as the proxy or pure play method